(3GdLQGFe GdeYdheGJjI aj GdbGfhf GdLRGFQj hGdjefj (B/s - (3ZdGH, aGjR eMeO QGLMs; (3hQOjI, fUQhfs (2011)
(3aj GdbGfhf GdLfGFj hGdYdhe GdLfGFjI(B.s
(3JfGhdJ gPg GdCWQhMI GdLQGFe GdeYdheGJjI aj GdbGfhf GdLRGFQj ShGA aj GdLGfH GdehVhYj habG dbGfhf GdeYdheGJ hLQGFe GdeGSI HGdfXe GdeYGdLI GdBdjI ddeYWjGJ Ce GdLGfH GdELQGFj habG dbGfhf GdELQGAGJ hbGfhf Jge (B(09-4) (3MSGe GdhbGjI ef LQGFe GdGJUGd hGdEYdGe hecGaMJge, hbO Je EjVGM MhGOK GdYUhQ aj GdbGfhf GdLRGFQj hHjfg GdeTQY Gdjefj deG jLH Cf jchf Ydjg GdhVY ef hVY JTQjY bGfhf GdehVhYj hELQGFj dehGLgI Jdc GdLQGFe, hbO TcdJ GdOQGSI Ydi ebGQfI GdYOjO ef GdbhGfjf dEjVGM Jdc GdLQGFe hehGLgJgG eUhQI CcKQ QNUI hefgG GdbGfhf GdSYhOj hGdEeGQGJj hGdfXQj hGdVeGfj hde JUd GdJTQjYGJ GdCLfHjI hajgG GdCef GdCeQjcj hGdQHWGFj GdjghOj hdPdc GdEJaGbGJ GdOhdjI hefgG EJaGbjI HhOGHSJ dSfI (B2001.s
(3ETQGa (B: (3hQOjI fUQhf(B.s
(3CWQhMIs
(3HHdjhLQGajI (B: (3U(B.s
Keywords: (3GdLQGFe GdMGShHjIs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs; (3GdLQGFe GdMGShHjIs -- (3bhGfjf hJTQjYGJs -- (3Gdjefs; (3QSGdI LGeYjI (B((3OcJhQGg(B)s